Well-shaped polymer nano- and micro-hybrid hairy particles fabricated via a facile one-step RAFT polymerization process. (11th June 2020) - Wenxun, Guan; Liming, Tang
Abstract: A facile and highly efficiency one-step method to fabricate well-shaped polymer nano- and micro-hybrid hairy particles (PHPs) is presented via reversible addition–fragmentation chain transfer (RAFT) polymerization of N, N′-methylene bisacrylamide (MBA) in solution containing ethanol as solubility regulator. Separated and slightly connected PHPs with uniform micrometer core particles densely attached by nanometer hairs could be obtained without additional regulatory measures. The structures and morphologies of the resulting products are conformed by various techniques. The morphological evolution process and polymerization solution are investigated and discussed in detail to understand the fabrication mechanism. Moreover, surface fluorescent modification of PHPs and the difference in adsorption performance between PHPs and bald particles are studied to demonstrate the potentiality of PHPs for further functionalization and application. Graphical abstract: Image 1 Highlights: Uniform polymer nano hairy particles is prepared by a facile one-step method. Micro cores and nano hairs can be successively formed without additional regulation. Oligomers with adequate sizes are the key to form fibrillary structures. Nano hairy particles can be functionalized based on remaining acrylamide groups. Nano hairy particles exhibit much higher adsorption capacity than bald particles.